Effects of isolated central nervous system involvement evaluated by multiparameter flow cytometry prior to allografting on outcomes of patients with acute lymphoblastic leukemia - Ma, Ling; Xu, Lan-Ping; Wang, Yu; Zhang, Xiao-Hui; Chen, Huan; Chen, Yu-Hong; Wang, Feng-Rong; Han, Wei; Sun, Yu-Qian; Yan, Chen-Hua; Lv, Meng; Tang, Fei-Fei; et al. (Frontiers in Oncology, 2023)
Introduction: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains a major strategy to cure patients with acute lymphoblastic leukemia (ALL). The aim of this study was to evaluate whether isolated flow cytometry (FCM)-positive central nervous system (CNS) involvement before allo-HSCT is clinically significant. Methods: The effects of isolated FCM-positive CNS involvement prior to transplantation on the outcomes of 1406 ALL patients with complete remission (CR) were retrospectively investigated. Results: Patients were classified into isolated FCM-positive CNS involvement (n=31), cytology-positive CNS involvement (n = 43), and negative CNS involvement (n = 1332) groups. Among the three groups, the 5-year cumulative incidence of relapse (CIR) values were 42.3%, 48.8%, and 23.4%, respectively (P<0.001). The 5-year leukemia-free survival (LFS) values were 44.7%, 34.9%, and 60.8%, respectively (P<0.001). Compared with the negative CNS group (n=1332), the 5-year CIR of the pre-HSCT CNS involvement group (n=74) was higher (46.3% vs. 23.4%, P<0.001], and the 5-year LFS was inferior (39.1% vs. 60.8%, P<0.001). Multivariate analysis indicated that four variables, T-cell ALL, in second complete remission or beyond (CR2+) at HSCT, pre-HSCT measurable residual disease positivity, and pre-HSCT CNS involvement, were independently associated with a higher CIR and inferior LFS. A new scoring system was developed using the following four variables: low-risk, intermediate-risk, high-risk, and extremely high-risk groups. The 5-year CIR values were 16.9%, 27.8%, 50.9%, and 66.7%, respectively (P<0.001), while the 5-year LFS values were 67.6%, 56.9%, 31.0%, and 13.3%, respectively (P<0.001). Conclusion: Our results suggest that ALL patients with isolated FCM-positive CNS involvement are at a higher risk of recurrence after transplantation. Patients with pre-HSCT CNS involvement had higher CIR and inferior survival outcomes.